2001
DOI: 10.1002/gps.481
|View full text |Cite
|
Sign up to set email alerts
|

Memory self‐appraisal and depressive symptoms in people at genetic risk for Alzheimer's disease

Abstract: These results confirm that mild depressive symptoms are related to subjective memory loss, but for some forms of memory complaint, the relationship holds true only for people without the major known genetic risk for Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
(29 reference statements)
2
24
1
1
Order By: Relevance
“…On the other hand, in a sample of people at familial risk for Alzheimer's disease, depression and memory complaints were more strongly associated in the absence of e4 [19]. In this sample we found no evidence for associations between SMI and e4 in participants either with or without depression.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…On the other hand, in a sample of people at familial risk for Alzheimer's disease, depression and memory complaints were more strongly associated in the absence of e4 [19]. In this sample we found no evidence for associations between SMI and e4 in participants either with or without depression.…”
Section: Discussioncontrasting
confidence: 44%
“…In one study, depression was found to be more strongly associated with SMI in the presence of e4 [2], but in another study the association was strongest in its absence [19].…”
Section: Introductionmentioning
confidence: 99%
“…The association between depressive symptoms and subjective memory complaints has been widely reported (Beck et al, 1974;Blackburn & Eunson, 1989;Derouesne et al, 1999;Small et al, 2001;Turvey et al, 2000). A number of components influence subjective memory complaints.…”
Section: Associations With Subjective Memorymentioning
confidence: 99%
“…Older adults with intact memory who self-report memory problems often have higher rates of depression (Turvey, Schultz, Arndt, Wallace, & Herzog, 2000). Subjective memory complaints may be the presentation of depression or may co-exist with depressive symptoms (Small et al, 2001) more often than with true cognitive decline (Derouesne et al, 1999;Jungwirth et al, 2004;Pearman & Storandt, 2004). However, the processes underlying the relationship between reports of memory loss and depressive symptoms are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Mutation of apoE has been linked to Alzheimer's disease (47); age-related memory disorders are also associated with apoE signaling (48). ApoE receptor signaling is directly involved in the dephosphorylation of tau protein and may have neuroprotective activity (49).…”
Section: Late Gene Expression Changes Of Mice In Enriched Environmentmentioning
confidence: 99%